Simplify #-4x(-5+4x)-2x#?

2 Answers
May 18, 2016

Answer:

#-4x(-5+4x)-2x=20x-8x^2#ko

Explanation:

#-4x(-5+4x)-2x#

= #(-4x)(-5)+(-4x)(4x)-2x#

= #20x+(-16x^2)-2x#

= #20x-16x^2-2x#

= #18x-16x^2#

Answer:

#-4x(-5+4x)-2x=color(blue)(-16x^2-18x)#

Explanation:

#-4x(-5+4x)-2x#

The expression inside the parentheses cannot be simplified further and there are no exponents.

Multiply #-4x# times the expression inside the parentheses.

#-4x(-5+4x)-2x=#

#20x-16x^2-2x#

Rewrite the expression in standard form.

#-16x^2+20x-2x#

Simplify.

#-16x^2+18x#